Tingkatan Keluhan Subjektif Berdasarkan Faktor Bahaya Fisik pada Pekerja Maintenance PT Besmindo Materi Sewatama - Friska Eka Fitria; Aidil Onasis (Jurnal Keselamatan Kesehatan Kerja dan Lingkungan, 2023)
Division worker Maintenance PT Besmindo Material Sewatama often complains of ringing in the ears, nausea, vomiting, weariness, short temper, and dizziness. The risk arising from the real-life workplace is the risk factor that is closely associated to this complaint. The aim of this research was to determine the level of severity of subjective complaints submitted by workers in the Maintenance department of PT Besmindo Material Sewatama according to actual workplace conditions. The time frame for this study was from March to July 2022. 52 persons made up the study's sample. Univariate analysis of the data was used in this study. According to the findings, there were a lot of subjective complaints based on the physical work environment (71.2%). Hot rooms, machine noise, and vibration from other work tools and machinery can lead to complaints. Engineering Control controls are required to lessen vibration and noise produced by the machine housed in the work area maintenance, and it is anticipated that workers would use PPE like earplugs to lower the noise level experienced by them.